Chitosan and Glyceryl Monooleate Nanostructures Containing Gemcitabine: Potential Delivery System for Pancreatic Cancer Treatment - Trickler, William J. (Springer US, 2010)
The objectives of this study are to enhance cellular accumulation of gemcitabine with chitosan/glyceryl monooleate (GMO) nanostructures, and to provide significant increase in cell death of human pancreatic cancer cells in vitro. The delivery system was prepared by a multiple emulsion solvent evaporation method. The nanostructure topography, size, and surface charge were determined by atomic force microscopy (AFM), and a zetameter. The cellular accumulation, cellular internalization and cytotoxicity of the nanostructures were evaluated by HPLC, confocal microscopy, or MTT assay in Mia PaCa-2 and BxPC-3 cells. The average particle diameter for 2% and 4% (w/w) drug loaded delivery system were 382.3 ± 28.6 nm, and 385.2 ± 16.1 nm, respectively with a surface charge of +21.94 ± 4.37 and +21.23 ± 1.46 mV. The MTT cytotoxicity dose-response studies revealed the placebo at/or below 1 mg/ml has no effect on MIA PaCa-2 or BxPC-3 cells. The delivery system demonstrated a significant decrease in the IC50 (3 to 4 log unit shift) in cell survival for gemcitabine nanostructures at 72 and 96 h post-treatment when compared with a solution of gemcitabine alone. The nanostructure reported here can be resuspended in an aqueous medium that demonstrate increased effective treatment compared with gemcitabine treatment alone in an in vitro model of human pancreatic cancer. The drug delivery system demonstrates capability to entrap both hydrophilic and hydrophobic compounds to potentially provide an effective treatment option in human pancreatic cancer.